A Study of Instructional Decisions and Lesson Planning Strategies of Highly Effective Rural Elementary School Teachers: Exploring effective instructional planning in rural elementary schools (Journal of Advances and Scholarly Researches in Allied Education, 2020)
A teacher must have more than just effective instructional planning skills. However, if planning techniques are inefficient or nonexistent, it is impossible to envisage a teacher experiencing high levels of learning for children. Learning how to plan for effective instruction is an important aspect of the work that an elementary school teacher does on a daily basis. While some new and struggling teachers in metropolitan school systems have access to professional development on a number of topics, including instructional planning, rural teachers sometimes struggle to obtain such opportunities. The goal of this project was to collect data and insights from rural instructors who have demonstrated experience in achieving high levels of student learning. They were studied for the precise planning decisions and actions they engaged in while planning. Not only were planning techniques discovered, but the reasons for their use were also looked at. This qualitative study used five excellent school teacher.